FAKTOR-FAKTOR YANG MEMENGARUHI REPEAT PURCHASE INTENTION PADA PENGGUNA APLIKASI SHOPEE DI JAKARTA - SERLY, SERLY; SEPTA HARYANTI, DENNY (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
The purpose of this study is to analyze as well as to determine the influence of Perceived Price and Quality of Delivery to Customer Satisfaction and Perceived Value, then Customer Satisfaction and Perceived Value to Repeat Purchase Intention on Shopee Application users in Jakarta. The method used in selecting samples in this research was convenience sampling, then data was taken from 219 respondents who were users and also those who made transactions via the Shopee application. Then, the method used in this research is PLS structural equation modeling (SEM). The results obtained in this research show that the Perceived Price has an influence on the Customer Satisfaction and also Perceived Value. The Quality of Delivery has an influence on the Customer Satisfaction and also Perceived Value. The Perceived Value has an influence on the Customer Satisfaction and Repeat Purchase Intention. The Customer Satisfaction has an influence on the Repeat Purchase Intention among Shopee application users in Jakarta.